880 Improving the Acute Knee Injury Pathway – A Regional Quality Improvement Project in the Oxford University Hospitals. (4th May 2021) - Kim, D; Neal-Smith, G; Wood, A
Abstract: Introduction: There are many patients being referred from A&E to orthopaedic trauma clinics in OUH for suspected ligament or meniscal damage, without convincing evidence of injury. This has led to demand for providing point of care ultrasound and streamlining of the referral process. Method: We conducted an audit of all A&E presentations at the OUH receiving a knee XR across 3 months and tracked their investigative and referral progress. Results: 477 knee XRs were performed 182/477 were referred from A&E to Trauma clinic. 57/182 of these received MRI. The remaining 125 were referred to physio or discharged. 35/57 who had MRI scans were referred to the specialist Acute Knee clinic. A total of 44 patients were seen at the Acute Knee clinic including an additional 9 patients from other referral pathways. Conclusions: Only 30% (57/182) patients referred to the Trauma clinic were deemed to have a serious ligament or meniscal injury. It is difficult to assess the extent of knee injury without specialist diagnostic equipment, which includes MRI or point of care ultrasound. This project has resulted in new trial protocols exploring the use of these technologies to improve this pathway.